Insights of asphaltene aggregation mechanism from molecular dynamics simulation (2015)
Asphaltene aggregation process was studied using molecular dynamics techniques. Four different structures were used. The first three molecules have a continental structure, with condensed aromatic cores, while the forth has an archipelago structure, with small groups of aromatic rings connected with saturated chains. The molecules were constructed in an atomistic framework, in which atoms are described individually. Interaction forces were calculated at 300 K and 200 atm; Van der Waals and electrostatic interactions were evaluated separately. For all four molecules the solubility parameter was calculated. It was found that Van der Waals interactions due to the presence of aromatic rings and electrostatic forces caused by the presence of heteroatoms such as oxygen, nitrogen and sulfur, are equally relevant in the aggregation of asphaltene molecules. For all molecules it was found asphaltene systems are more stable in aggregation state than in monomeric state. For continental structures, the presence of long ramifications obstructs the formation of asphaltene aggregates. For archipelago structures, the flexibility of the molecules enables the aggregation with other structures. The presence of heteroatoms creates a repulsive force that hinders the aggregation process. The molecular volume and the cohesive energy are also sensitive to the geometric configuration and the composition of the species, which affects the solubility parameter.